CFD-informed surrogate modeling for rapid prediction of coupled pavement–air thermal response - Hamidreza Alinejad; Junsuk Kang; Junmo Lee; Young Sun Kwon; Seunghun Baek; Jung-Min Lee; Sang Rae Kim (Building and Environment, 2026)

Concentrations and formation pathways of nitrogen-containing organic compounds in PM2.5 from Seoul and Beijing - Ju Young Kim; Yong Pyo Kim; Xu Yu; Jianzhen Yu; Zhijun Wu; Hyung-Min Lee; Mijung Song; Kyoung Soon Jang; Changhyuk Kim; Na Rae Choi; Ji Yi Lee (Environmental Research, 2025)

Quantitative analysis of PM2.5 oxidative potential: Insights into the role of organic compounds and sources - Ji-Hyeon Koo; Sung-Won Park; Hyo-Won Lee; Pyung-Rae Kim; Ji-Won Jeon; Kyung-Hwan Kwak; Seung-Muk Yi; Jeffrey L. Collett; Young-Ji Han (Journal of Hazardous Materials, 2025)

Estimation of Potentially Toxic Substances and Health Risks in VOCs in Urban Areas of Seoul - Shin-Young Park; Hyeok Jang; Kwang-rae Kim; Hyun-ju Ha; Yuri Choi; Seung-mi Kwon; Yongsuk Choi; Ju-Sung Park; Cheol-Min Lee (Water, Air, & Soil Pollution, 2025)

Erratum: Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2025)

Characteristics of elevated PM2.5 events driven by enhanced organic compound concentrations in a South Korean residential city - Hye-Ji Lee; Hyo-Won Lee; Sung-Won Park; Ji-Won Jeon; Pyung-Rae Kim; Kyung-Hwan Kwak; Young-Ji Han; Thomas M. Holsen; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Jung-Min Park; et al. (Atmospheric Environment, 2025)

Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2024)

Capabilities of satellite Geostationary Environment Monitoring Spectrometer (GEMS) NO2 data for hourly ambient NO2 exposure modeling - Hyung Joo Lee; Na Rae Kim; Min Young Shin (Environmental Research, 2024)

Corrigendum to “Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays” [920 (2024) 171053] - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

In Situ Immobilization of Potentially Toxic Elements in Arable Soil by Adding Soil Amendments and the Best Ways to Maximize Their Use Efficiency - Chaw Su Lwin; Young-Nam Kim; Mina Lee; Ha-il Jung; Kwon-Rae Kim (Journal of Soil Science and Plant Nutrition, 2024)

Determination of average growth rate based on statistical relationships using geomorphological and geotechnical variables in predictive debris flow simulations - Joon-Young Park; Seok Yoon; Deuk-Hwan Lee; Seung-Rae Lee; Hwan-Hui Lim (Geomorphology, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Sorption of As, Cd, and Pb by soil amendments: in situ immobilization mechanisms and implementation in contaminated agricultural soils - Chaw Su Lwin; Young-Nam Kim; Mina Lee; Kwon-Rae Kim (Environmental Science and Pollution Research, 2023)

Eye development and developmental expression of crystallin genes in the long arm octopus, Octopus minor - Kyoung-Bin Ryu; Gun-Hee Jo; Young-Chun Gil; Donggu Jeon; Na-Rae Choi; Seung-Hyun Jung; Seonmi Jo; Hye Suck An; Hae-Youn Lee; Seong-il Eyun; Sung-Jin Cho (Frontiers in Marine Science, 2023)
The eye of a cephalopod is a well-known example of convergent evolution and resembles the vertebrate eye. Although cephalopods and vertebrates exhibit similar eye form and function, they differ in visual origin and structure. The common long-arm octopus ( Octopus minor ) is a good model system in evolutionary and developmental studies due to its highly centralized nervous system, shorter life cycle, and specific camera-type eyes that contribute to convergence with vertebrate eye. Lens-containing eyes represent a significant improvement of simple eye and have evolved by convergent mechanisms, a variety of lenses and corneas containing diverse crystallin. The diversity and taxon-specificity of lens crystallin is indicative of convergent evolution of crystallin roles. Previous studies have focused on morphological, ontogenetic and phylogenetic analysis of crystallin to understand the evolution of lens-containing eyes. However, little is known about the functional analysis of taxon-specific crystallin genes at the molecular level in the eye of O. minor . Using an embryonic staging system of Octopus minor as a model system, we investigated fifteen genomes and the structure of eye by immunohistochemistry, phalloidin staining and the three-dimensional structures. We also obtained the crystallin-related genes ( i . e ., α-, S-, and Ω-crystallin) from the transcriptome data of O. minor . Subsequent molecular phylogenetic analysis based on these genes revealed a distinct divergence pattern among the three gene classes and further suggested the evidence supporting the taxon-specific convergent evolutionary trend. We analyzed the expression pattern of crystallin genes via in situ hybridization during developmental stages. All crystallin genes are commonly expressed in the lentigenic cells of ciliary body. The α-crystallin found in cephalopods was also expressed at the peripheral region of the lens including ciliary body, suggesting a possible role in lens formation in cephalopods. This study will provide information on the eye development of O. minor and support the typical models of convergent evolution by demonstrating independent recruitment of different types of proteins to fulfill their unique visual role.

First report of pitaya virus X infecting dragon fruit (Selenicereus undatus) in Korea - Nam-Yeon Kim; Yong Hun Jo; Young Min Bae; Kyung-Pyo Lee; Rae-Dong Jeong; Yeon Soo Han; KiBeom Park (Journal of Plant Pathology, 2023)

Atmospheric saccharide composition and its possible linkage with marine phytoplankton from North Pacific to the Antarctic regions - Ki Ae Kim; Na Rae Choi; Ha Young Yoo; Eunho Jang; Young Jun Yoon; Jiyeon Park; Chang Hoon Jung; Yong Pyo Kim; Ki-Tae Park; Ji Yi Lee (Atmospheric Environment, 2023)

Synergetic effect of complex soil amendments to improve soil quality and alleviate toxicity of heavy metal(loid)s in contaminated arable soil: toward securing crop food safety and productivity - Young-Nam Kim; Keum-Ah Lee; Mina Lee; Kwon-Rae Kim (Environmental Science and Pollution Research, 2022)

Coexistence of Cr and Ni in anthropogenic soils and their chemistry: implication to proper management and remediation - Chaw Su Lwin; Young-Nam Kim; Mina Lee; Kwon-Rae Kim (Environmental Science and Pollution Research, 2022)

Assessment of barrier location effect on debris flow based on smoothed particle hydrodynamics (SPH) simulation on 3D terrains - Shin-Kyu Choi; Joon-Young Park; Deuk-Hwan Lee; Seung-Rae Lee; Yun-Tae Kim; Tae-Hyuk Kwon (Landslides, 2021)
Debris flows are one of the perilous landslide-related hazards due to their fast flow velocity, large impact force, and long runout, in association with poor predictability. Debris-flow barriers that can minimize the energy of debris flows have been widely constructed to mitigate potential damages. However, the interactions between debris flows and barriers remain poorly understood, which hampers the optimal barrier installation against debris flows. Therefore, this study examined the effect of barrier locations, in particular source-to-barrier distance, on velocity and volume of debris flows via the numerical approach based on smoothed particle hydrodynamics (SPH). A debris-flow event was simulated on a 3D terrain, in which a closed-type barrier was numerically created at predetermined locations along a debris-flow channel, varying the source-to-barrier distance from the initiation point. In all cases, the closed-type barrier significantly reduced the velocity and volume of the debris flows, compared to the cases without a barrier. When the initial volume of source debris was small, or when the flow path was short, the barriers effectively blocked the debris flow regardless of the source-to-barrier distance. However, with a long flow path, installation of the barrier closer to the initiation location appeared more effective by preventing the debris volume from growing by entrainment. Our results contribute to a better understanding of how source-to-barrier distance influences debris-flow behavior, and show that the methodology presented herein can be further used to determine optimum and efficient designs for debris-flow barriers.

Dieckol or phlorofucofuroeckol extracted from Ecklonia cava suppresses lipopolysaccharide-mediated human breast cancer cell migration and invasion - Young-Ju Lee; Jung-Hwan Park; Sang-Ah Park; Na-Rae Joo; Bong Ho Lee; Kyung Bok Lee; Sang-Muk Oh (Journal of Applied Phycology, 2020)

Sea Cucumber Stichopus japonicus Hydrolysate Alleviates Late-onset-hypogonadism in Aged SD Rats - Jong-Min Lim; Young Dae Kim; Young Suk Kim; Hyung-Rae Cho; Kwang Ho Lee; Il Joo Yoon; Sung Kew Kim; Myoung Seok Kim; Jae-Suk Choi (Toxicology and Environmental Health Sciences, 2019)

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Perfluorooctane sulfonate exacerbates mast cell-mediated allergic inflammation by the release of histamine - Jun-Kyoung Lee; Soyoung Lee; Young-Ae Choi; Meiling Jin; Yeon-Yong Kim; Byeong-Cheol Kang; Min-Jong Kim; Hima Dhakal; Sang-Rae Lee; Sun-Uk Kim; Dongwoo Khang; Sang-Hyun Kim (Molecular & Cellular Toxicology, 2018)

Effects of backcrossing on quality of strawberry fruit - Sun Yi Lee; Seung Yu Kim; Dae Young Kim; Ho Jeong Jeong; In Seok Um; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2018)

Combined Poly(Lactide-Co-Glycolide) Microspheres Containing Diphtheria Toxoid for a Single-shot Immunization - Hye Seung Woo; Sung Rae Kim; Mikyeong Yoon; Eun Seok Lee; In Ho Chang; Young Mi Whang; Do Ik Lee; Myung Joo Kang; Young Wook Choi (AAPS PharmSciTech, 2018)

Wart-like spot formation on the fronds of Chondrus ocellatus (Gigartinales) by a brown alga, Mikrosyphar zosterae (Ectocarpales) in Korea - Cyr Abel Maranguy Ogandaga; Yeon Ju Na; Sang-Rae Lee; Young Sik Kim; Han Gil Choi; Ki Wan Nam (Journal of Applied Phycology, 2017)

Ssanghwa-Tang, a traditional herbal formula, suppresses cigarette smoke-induced airway inflammation via inhibition of MMP-9 and Erk signaling - Je-Won Ko; Na-Rae Shin; Sung-Hyeuk Park; In-Chul Lee; Jung-Min Ryu; Young-Kwon Cho; Jong-Choon Kim; Chang-Seob Seo; In-Sik Shin (Molecular & Cellular Toxicology, 2017)

Infection and cox2 sequence of Pythium chondricola (Oomycetes) causing red rot disease in Pyropia yezoensis (Rhodophyta) in Korea - Soon Jeong Lee; Bo Young Jee; Maeng-Hyun Son; Sang-Rae Lee (Algae, 2017)

Behavioral responses of chinstrap and gentoo penguins to a stuffed skua and human nest intruders - Won Young Lee; Jin-Woo Jung; Han-Gu Choi; Hosung Chung; Yeong-Deok Han; Sam-Rae Cho; Jeong-Hoon Kim (Polar Biology, 2017)

Occurrence and diversity of tetracycline resistance genes in the agricultural soils of South Korea - Song Yeob Kim; Saranya Kuppusamy; Jang Hwan Kim; Young-Eun Yoon; Kwon-Rae Kim; Yong Bok Lee (Environmental Science and Pollution Research, 2016)

Systematic identification of novel biomarker signatures associated with acquired erlotinib resistance in cancer cells - Young Seok Lee; Jin Ki Kim; Tae Hwan Park; Young Rae Kim; Ho Sung Myeong; Kang Kwon; Young Tae Ro; Yun Hee Noh; Sung Young Kim (Molecular & Cellular Toxicology, 2016)

Antibacterial Mechanism of (−)-Nortrachelogenin in Escherichia coli O157 - Heejeong Lee; Young Rae Ji; Zae Young Ryoo; Myung-Sook Choi; Eun-Rhan Woo; Dong Gun Lee (Current Microbiology, 2016)

The role of biochar, natural iron oxides, and nanomaterials as soil amendments for immobilizing metals in shooting range soil - Anushka Upamali Rajapaksha; Mahtab Ahmad; Meththika Vithanage; Kwon-Rae Kim; Jun Young Chang; Sang Soo Lee; Yong Sik Ok (Environmental Geochemistry and Health, 2015)

A nationwide survey and genetic analysis of rice stripe virus in South Korea during 2012–2013 - Sang-Yun Cho; Rae-Dong Jeong; Young-Nam Yoon; Dong Bum Shin; Hang-Won Kang; Bong Choon Lee (Journal of General Plant Pathology, 2015)

Characterization and chemical control of soft rot disease caused by Pantoea sp. strain PPE7 in Pleurotus eryngii mushroom crops - Min Keun Kim; Song Hee Lee; Young Han Lee; HyeRan Kim; JeongYeo Lee; Il Rae Rho (European Journal of Plant Pathology, 2015)

Laxative effects of fermented rice extract (FRe) in normal rats - Jae-Suk Choi; Joo-Wan Kim; Hyung-Rae Cho; Ki-Young Kim; Jong-Kwang Lee; Sae-Kwang Ku; Jae Hak Sohn (Toxicology and Environmental Health Sciences, 2014)

Chlorophyll fluorescence as a diagnostic tool for abiotic stress tolerance in wild and cultivated strawberry species - Young-Wang Na; Ho Jeong Jeong; Sun-Yi Lee; Hyo Gil Choi; Seok-Hyeon Kim; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2014)

Ticks collected from migratory birds, including a new record of Haemaphysalis formosensis, on Jeju Island, Korea - Chang-Yong Choi; Chang-Wan Kang; Eun-Mi Kim; Sang Lee; Kyoung-Ha Moon; Mi-Rae Oh; Takeo Yamauchi; Young-Min Yun (Experimental and Applied Acarology, 2014)

Development of renal extracellular matrix (ECM) scaffold for kidney regeneration - Seon Yeong Chae; So Young Chun; Min Park; Yu-Jin Jang; Jin Rae Kim; Se Heang Oh; Jin Ho Lee; Phil Hyun Song; Tae Gyun Kwon; Tae-Hwan Kim (Tissue Engineering and Regenerative Medicine, 2014)

Inclusion compound formulation of hirsutenone with beta-cyclodextrin - Byeong Kil Ahn; Sang Gon Lee; Sung Rae Kim; Dong Hoon Lee; Myung Hwan Oh; Min Won Lee; Young Wook Choi (Journal of Pharmaceutical Investigation, 2013)

Topical formulation of retinyl retinoate employing nanostructured lipid carriers - Sang Gon Lee; Jae Han Jeong; Sung Rae Kim; Kyung Min Lee; Byeong Kil Ahn; Mean Hyung Kang; Young Wook Choi (Journal of Pharmaceutical Investigation, 2012)

Overexpression of Jazf1 induces cardiac malformation through the upregulation of pro-apoptotic genes in mice - Ki Beom Bae; Myoung Ok Kim; Dong Hoon Yu; Mi Jung Shin; Hei Jung Kim; Hyung Soo Yuh; Young Rae Ji; Jae-Young Kim; Jin Man Kim; Byung Hwa Hyun; Hwi Cheul Lee; Won Kyong Chang; et al. (Transgenic Research, 2011)

Cadmium resistance in tobacco plants expressing the MuSI gene - Young-Nam Kim; Ji-Seoung Kim; Sang-Gyu Seo; Youngwoo Lee; Seung-Woo Baek; Il-Sup Kim; Ho-Sung Yoon; Kwon-Rae Kim; Sun-Hyung Kim; Kye-Hoon Kim (Plant Biotechnology Reports, 2011)

Apoptosis Signal-Regulating Kinase1 is Inducible by Protein Kinase Cδ and Contributes to Phorbol Ester-Mediated G1 Phase Arrest Through Persistent JNK Activation - Young-Rae Kim; Hee Sun Byun; Juhee Jeon; Byung Lyul Choi; Kyeong Ah Park; Minho Won; Tiejun Zhang; Sanghee Shin; Hyunji Lee; Junseo Oh; Gang Min Hur (Cell Biochemistry and Biophysics, 2011)

Comparison of Nitrogen Fixation for North- and South-facing Robinia pseudoacacia Stands in Central Korea - Nam Jin Noh; Yowhan Son; Jin Woo Koo; Kyung Won Seo; Rae Hyun Kim; Yoon Young Lee; Kyung Seun Yoo (Journal of Plant Biology, 2010)

Molecular characterization of OsPAP2: transgenic expression of a purple acid phosphatase up-regulated in phosphate-deprived rice suspension cells - Yeon Jae Hur; Byung Rae Jin; Jaesung Nam; Young Soo Chung; Jai Heon Lee; Hong Kyu Choi; Dae Jin Yun; Gihwan Yi; Yong Hwan Kim; Doh Hoon Kim (Biotechnology Letters, 2010)

Comparison Between Shear Behaviors of Overconsolidated Nakdong River Sandy Silt and Silty Sand - Khin Swe Tint; Seung Rae Lee; Young Su Kim (Marine Georesources & Geotechnology, 2009)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Polymorphism and Genomic Structure of the A+T-Rich Region of Mitochondrial DNA in the Oriental Mole Cricket, Gryllotalpa Orientalis (Orthoptera: Gryllotalpidae) - Iksoo Kim; So Young Cha; Mi Ae Kim; Young Shin Lee; Kwang Sik Lee; Yong Soo Choi; Jae Sam Hwang; Byung Rae Jin; Yeon Soo Han (Biochemical Genetics, 2007)

Biomass accumulations and the distribution of nitrogen and phosphorus within threeQuercus acutissima stands in central Korea - Nam Jin Noh; Yowhan Son; Rae Hyun Kim; Kyung Won Seo; Jin Woo Koo; In Hyeop Park; Young Jin Lee; Kyeong Hak Lee; Yeong Mo Son (Journal of Plant Biology, 2007)

Membrane cholesterol is required for activity of Vibrio vulnificus cytolysin - Hong-Nu Yu; Young-Rae Lee; Kwang-Hyun Park; So-Young Rah; Eun-Mi Noh; Eun-Kyung Song; Myung-Kwan Han; Byeong-Soo Kim; Sung-Ho Lee; Jong-Suk Kim (Archives of Microbiology, 2007)

Reproducibility of Quantitative Estimate of Magnetocardiographic Ventricular Depolarization and Repolarization Parameters in Healthy Subjects and Patients with Coronary Artery Disease - Hyun Kyoon Lim; Namsik Chung; Kiwoong Kim; Young-Guk Ko; Hyukchan Kwon; Yong-Ho Lee; Jin-Bae Kim; Jung Rae Cho; Jin-Mok Kim; In-Seon Kim; Yong Ki Park (Annals of Biomedical Engineering, 2006)

Temperature Effect on Migration of Zn and Cd Through Natural Clay - Nam Young Do; Seung Rae Lee (Environmental Monitoring and Assessment, 2006)

A Serine Protease Gene from the Firefly, Pyrocoelia rufa: Gene Structure, Expression, and Enzyme Activity - Jianhong Li; Young Moo Choo; Kwang Sik Lee; Yeon Ho Je; Soo Dong Woo; Iksoo Kim; Hung Dae Sohn; Byung Rae Jin (Biotechnology Letters, 2005)

Low density lipoprotein inactivates Vibrio vulnificus cytolysin through the oligomerization of toxin monomer - Kwang-Hyun Park; Haet-Bit Yang; Hyung-Gue Kim; Young-Rae Lee; Hyoun Hur; Jong-Soo Kim; Bon-Sun Koo; Myung-Kwan Han; Jong-Hyun Kim; Young-Ju Jeong; Jong-Suk Kim (Medical Microbiology and Immunology, 2005)

Cloning and characterization of the Cu,Zn superoxide dismutase (SOD1) cDNA from the mole cricket, Gryllotalpa orientalis - Iksoo Kim; Kwang Sik Lee; Young Soo Choi; Jae Sam Hwang; Hung Dae Sohn; Byung Rae Jin (Biotechnology Letters, 2005)

Mitochondrial DNA Sequence-Based Population Genetic Structure of the Firefly, Pyrocoelia rufa (Coleoptera: Lampyridae) - Sang-Chul Lee; Jin-Sik Bae; Iksoo Kim; Hirobumi Suzuki; Seong-Ryul Kim; Jong-Gill Kim; Keun-Young Kim; Won-Jin Yang; Sang-Mong Lee; Hung-Dae Sohn; Byung-Rae Jin (Biochemical Genetics, 2003)

Effect of Temperature on Single and Competitive Adsorptions of Cu(II) and Zn(II) onto Natural Clays - Nam Young Dho; Seung Rae Lee (Environmental Monitoring and Assessment, 2003)

Cloning of the fibroin gene from the oak silkworm, Antheraea yamamai and its complete sequence - Jae-Sam Hwang; Jin-Sung Lee; Tae-Won Goo; Eun-Young Yun; Kwang-Sik Lee; Yong-Sung Kim; Byung-Rae Jin; Sang-Mong Lee; Keun-Young Kim; Seok-Woo Kang; Dong-Sang Suh (Biotechnology Letters, 2001)